Development of a Room Temperature-Operable PbS QD-Based Infrared Sensor by Using Bandgap Manipulation - Kim, Sihyeok; Lee, Keekeun (Journal of the Korean Physical Society, 2018)
A PbS quantum dot (QD)-based infrared sensor was developed for room temperature operability by using interlayer energy bandgap manipulation. The developed sensor constitutes various ratios of PbS QDs in a PCPDTBT matrix that are sandwiched by two metal electrodes. The offset barrier exerted a great effect on the sensitivity improvement. The PbS QD mixture ratio, layer stacking order, and sensitive layer thickness were controlled for optimization. The absorption characterization and the transmission electron microscopy analysis revealed the energy bandgap and the diameter of the PbS QDs.
Keywords: Bandgap manipulation; Infrared sensor; Organic polymer; PbS quantum dot